2021
DOI: 10.1016/j.gore.2021.100830
|View full text |Cite
|
Sign up to set email alerts
|

Impact of positive cytology in uterine serous carcinoma: A reassessment

Abstract: Highlights Prognostic implications of peritoneal cytology in uterine serous cancer are unclear. Positive cytology is not associated with FIGO stage or LVSI. Peritoneal cytology is an independent prognosticator in uterine serous cancer. Positive cytology is independently associated with worse overall survival and ECSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 39 publications
3
8
0
Order By: Relevance
“…Multivariate analysis in our study also suggested that malignant peritoneal cytology was an independent risk factor for both PFS and OS. These findings are consistent with two previous reports focusing on non-endometrioid EC [ 11 , 14 ]. Matsuo et al reported that the mortality risk is nearly tripled (HR 2.59) with a 5-year survival rate decrease of 19.4% in stage I non-endometrioid EC patients with malignant peritoneal cytology [ 11 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Multivariate analysis in our study also suggested that malignant peritoneal cytology was an independent risk factor for both PFS and OS. These findings are consistent with two previous reports focusing on non-endometrioid EC [ 11 , 14 ]. Matsuo et al reported that the mortality risk is nearly tripled (HR 2.59) with a 5-year survival rate decrease of 19.4% in stage I non-endometrioid EC patients with malignant peritoneal cytology [ 11 ].…”
Section: Discussionsupporting
confidence: 94%
“…One study reported that diagnosis at an older age (>78 years old), serous histology, and larger tumor size were associated with increased risks of malignant peritoneal cytology [ 11 ]. Other studies, however, have failed to find an association between clinical-pathological factors and malignant peritoneal cytology [ 12 , 14 ]. A meta-analysis demonstrated that hysteroscopy is associated with a higher rate of positive peritoneal cytology when compared with no hysteroscopy, but this phenomenon is not identified in early-stage EC [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study out of Michigan examined a cohort of 148 women with USC and found that 22% of the cohort had positive washings. The presence of malignant cytology in this study was significantly associated with recurrence and overall survival (HR 2.09, 95% CI [1.19-3.68]) [ 17 ]. A large Surveillance, Epidemiology, and End Results database study of over 14,000 patients with uterine cancer identified that five-year disease-specific survival for women with negative cytology was significantly better than those with positive cytology (95.1% vs 80.8% in endometrioid adenocarcinoma and 78.0% vs 50.4% in clear cell or serous carcinoma) [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a study based on the Surveillance, Epidemiology, and End Results database showed that positive peritoneal washings predict decreased survival 6 . Focusing on the histological type, positive cytology was reported to be a prognostic factor in serous uterine cancer 16 …”
Section: Introductionsmentioning
confidence: 99%